Durability of 4H-SiC Schottky power diodes irradiated with high-energy bombarding electrons - Mohd Khairi, Mohamad Azim; Abdullah, Yusof; Ab Rahim, Rosminazuin; Hasbullah, Nurul Fadzlin (The Institution of Engineering and Technology (IET), 2019)
A performance comparison of high-voltage SiC Schottky power diodes from ROHM Co., and CREE, Inc., is reported. The diodes were irradiated by high-energy, 3.0 MeV, electrons within a fluence ranging from 6.6×1015 to 4.95×1016 electron/cm2 . Current density-voltage and capacitance-voltage characterization were used to investigate the impact of the irradiation on ideality factor, saturation current, series resistance, and barrier height. The results show that the forward current decreased with increasing irradiation, while the reverse current increased except for the diodes irradiated with 4.95×1016 electron/cm2 . The ideality factors increased more significantly at the highest fluence compared to the other fluences i.e. from 1.026 (ROHM) and 1.01 (CREE) at before irradiation to 1.2 (ROHM) and 1.8 (CREE) at 4.95×1016 electron/cm2 . The saturation currents increased until the fluence of 1.6×1016 electron/cm2 , then decreased after 3.3×1016 electron/cm2 which lead to the opposing behaviour observed in barrier height. Subsequently, the series resistances showed a significant rise for both models and are interpreted as being due to the changes in the free carriers’ concentration during irradiation. The capacitance of both models was reduced after irradiation, proving that the free carriers’ concentration has been decreased with increasing fluence due to the trapping effect of the defects.